Exploring the relationship between urbanized Malaysian youth and their mobile phones: a quantitative approach - Balakrishnan, Vimala; Raj, Ram Gopal (Elsevier, 2011)
Mobile phones have become a ubiquitous consumer item. This paper aims to explore mobile phone usage, extending work beyond teenage years to examine the role of mobile phones among urbanized Malaysian youth, specifically university students. Four main categories were identified, namely, mobile phone purchasing factors and reasons to use, mobile phone usage and also behavioral issues. A mixed-mode approach involving questionnaire surveys and 24-h diaries were used to gather the relevant data. A total of 417 respondents participated in this study. The salient results indicate respondents in this study consider brand, trend and price to be the three most important purchasing factors while socializing and privacy emerged as the two most important reasons to use mobile phones. Behavioral issues related to addiction and inappropriate use of mobile phones was also observed among the respondents. Gender analysis revealed females to use their mobile phones more to socialize, gossip and as a safety device. The findings of this study could prove to be beneficial to those exploring the mobile phone adoption and usage pattern in a developing country such as Malaysia.